Specificities and redundancies in the NEL family of bacterial E3 ubiquitin ligases of Salmonella enterica serovar Typhimurium - Bullones-Bolaños, Andrea; Martín-Muñoz, Paula; Vallejo-Grijalba, Claudia; Bernal-Bayard, Joaquín; Ramos-Morales, Francisco (Frontiers in Immunology, 2024)
Salmonella enterica serovar Typhimurium expresses two type III secretion systems, T3SS1 and T3SS2, which are encoded in Salmonella pathogenicity island 1 (SPI1) and SPI2, respectively. These are essential virulent factors that secrete more than 40 effectors that are translocated into host animal cells. This study focuses on three of these effectors, SlrP, SspH1, and SspH2, which are members of the NEL family of E3 ubiquitin ligases. We compared their expression, regulation, and translocation patterns, their role in cell invasion and intracellular proliferation, their ability to interact and ubiquitinate specific host partners, and their effect on cytokine secretion. We found that transcription of the three genes encoding these effectors depends on the virulence regulator PhoP. Although the three effectors have the potential to be secreted through T3SS1 and T3SS2, the secretion of SspH1 and SspH2 is largely restricted to T3SS2 due to their expression pattern. We detected a role for these effectors in proliferation inside fibroblasts that is masked by redundancy. The generation of chimeric proteins allowed us to demonstrate that the N-terminal part of these proteins, containing the leucinerich repeat motifs, confers specificity towards ubiquitination targets. Furthermore, the polyubiquitination patterns generated were different for each effector, with Lys48 linkages being predominant for SspH1 and SspH2. Finally, our experiments support an anti-inflammatory role for SspH1 and SspH2.